THE DIFFERENCES IN TOTAL CHOLESTEROL LEVELS OF SMOKERS AND NON-SMOKERS IN PRIVATE DELIVERY SERVICE EMPLOYEES IN BANTARGEBANG, BEKASI CITY - Setiawan, Heru; Lestari, Puji; Aulia, Alfina (Jurnal Fisioterapi dan Kesehatan Indonesia, 2024)
Smoking behavior is a habit that is often found in everyday life in people in various places and one of the elements that can raise blood cholesterol levels. Nicotine is the main component in cigarettes that plays a role in increasing free fatty acids so that LDL levels become high. Another chemical found in cigarettes, acrolein, can damage HDL, thus disrupting HDL's task in collecting LDL. This study aims to determine the average difference in total cholesterol levels between smokers and non-smokers in private delivery service employees in Bantargebang, Bekasi City. This research method using an unpaired comparative analytic experimental method of 2 groups. The data analysis used is the Independent T test. The results of this study the average total cholesterol levels of each sample group of 25 respondents for smokers and non-smokers were 216.6 mg/dL and 179.2 mg/dL. Smokers who had been smoking for more than 10 years and who smoked between 11 and 21 cigarettes per day had total cholesterol levels above normal. Conclusion in this study found a significant difference in average total cholesterol levels between smokers and non-smokers in private delivery service employees in Bantargebang Bekasi City with a level of significance (α = 5%) (p=0.000). In smokers, nicotine and acrylonitrile are the main components that play a role in the occurrence of lipid disorders in the body.